2019
DOI: 10.1186/s12889-019-6580-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening and supporting through schools: educational experiences and needs of adolescents living with HIV in a South African cohort

Abstract: Background Many adolescents living with HIV remain disconnected from care, especially in high-prevalence settings. Slow progressors–adolescents infected perinatally who survive without access to lifesaving treatment–remain unidentified and disconnected from heath systems, especially in high-prevalence settings. This study examines differences in educational outcomes for ALHIV, in order to i) identify educational markers for targeting HIV testing, counselling and linkages to care, and ii) to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 43 publications
(38 reference statements)
6
36
2
1
Order By: Relevance
“…In the TEEWA survey, school attendance was high, above 85%, for both ALPHIV and controls, in the upper range compared to other studies in various age groups (8)(9)(10)(11)(12)14). However, among adolescents living in family settings, school attendance was lower among ALPHIV than among general population controls (83% vs. 94%, respectively).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In the TEEWA survey, school attendance was high, above 85%, for both ALPHIV and controls, in the upper range compared to other studies in various age groups (8)(9)(10)(11)(12)14). However, among adolescents living in family settings, school attendance was lower among ALPHIV than among general population controls (83% vs. 94%, respectively).…”
Section: Discussionmentioning
confidence: 57%
“…Studies carried out in low-income countries also found a significant association between HIV-infection and disrupted schooling after adjustment on socio-economic factors (8,9,14). In a recent study in South Africa, Fotso et al found that HIV-infection significantly reduced adolescent school attainment and that contextual factors could only explain 18% of the attainment gap (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, 10-19-year-old apparently HIV-negative adolescents who were either living in the same home or a neighbouring home were also interviewed. HIV status was ascertained using a sequential elimination process (34). Firstly, we searched patient les and Tier.net records in all participating health facilities.…”
Section: Methodsmentioning
confidence: 99%